Mensuração dos custos logísticos em uma operação com carga sólida em um porto público do Nordeste brasileiro - Medeiros, Mayara (2018)
The port sector presents a great space in the world scope and local. The Brazilian’s port sector has gone through constant formulations to try to adapt to the world scenario. The last impact was with the Law 12815/13, called the new port’s law, launched with the aim of automatically disclosing the creation of terminals for private use (TUP). From this, arises the need to obtain better efficiency from the ports in order to be able to stand out from the competition. The objective of this work is to measure the logistic costs in a solid cargo operation, of the Petcoke, in the public dock of the Northeast Public’s port. To accomplish this, it was necessary to map the logistics chain of the Petcoke, to identify the agents involved in the process, raise the activities and resources involved, apply the activity-based cost method (ABC) and segregate the logistics’ costs found on the chain. For the theoretical framework a systematic literature review (SLR) were carried out in order to contemplate aspects related to logistics, port logistics, cost management, logistics costs and port legislation. Semi-structured interviews were conduct in data collection previously validated with experts from the port sector and with agents external to the chain. Each instrument was addressed to each of the agents and besides the interviews some cargo observations were made followed up with someone involved in the process and some analysis of documents available in port and in the company. At the end of each interview and observation a compilation and crossing of the data together with the documentary analysis was performed. As previously mentioned, ABC method was used to measure the costs. It was possible to map the Petcoke chain in general and detailed by agent, as well as to find the logistics costs of the agents involved and segregate the port logistics costs of some of these agents. It was possible to detect that the agent with the lowest percentage of logistic costs was the trading with 94.95% and the agent with the highest percentage of port’ logistics costs was the port operator with 99.74%.